Korelasi stres subjektif dan strategi koping mahasiswa keperawatan di masa pandemi Covid-19 - Lainsamputty, Ferdy; Wuisang, Metty (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Stress is common among nursing students, especially those in their final year. If it is not handled properly, in the long term it will disrupt physical health and the clinical learning process will be hampered. This condition is exacerbated by the pandemic situation which increases the risk of students contracting infectious diseases during clinical practice. Various factors are also potentially related to nursing students' coping strategies.Purpose: To examine the correlation between stress and nursing students' coping strategies during the Covid-19 pandemic, along with the factors related to it.Method: A descriptive analytical design with a cross-sectional approach was used in this study involving 104 nursing students. The measuring instruments used are Depression Anxiety Stress Scale-42 (DASS-42) and Coping Strategies Inventory-Short Form (CSI-SF). Statistical tests use Independent T-Test, One-way ANOVA, and Pearson Correlation.Results: There was a difference in the average score of the coping strategy component involvement (t=-3.01; p=0.01) and disinvolvement (t=-0.26; p=0.01) based on the use of personal protective equipment (PPE). There was a difference in scores for the components of engagement coping strategies based on knowledge and prevention about Covid-19 (t=-2.45; p=0.02). There was a significant correlation between age and disengagement (r=-0.32; p<0.01) and emotion-focused disengagement (r=-0.41; p<0.001). Stress was significantly correlated with the emotion-focused component of disengagement (r=0.33; p<0.01).Conclusion: Students who are older, who use PPE have sufficient knowledge and prevention regarding Covid-19, and who experience more severe stress tend to use better coping strategies.Suggestion: Students should be able to manage stress and use positive coping strategies. Assessment of the student's psychological condition can be considered to continue during the study. Future research can develop interventions for the use of appropriate coping strategies in nursing students. Keywords: Coping Strategy; Nursing Students; Subjective Stress. Pendahuluan: Stres umum didapati pada mahasiswa keperawatan, khususnya yang berada di tahun terakhir. Apabila tidak tertangani dengan baik, dalam jangka panjang maka akan mengganggu kesehatan fisik dan proses pembelajaran klinik menjadi terhambat. Kondisi ini diperparah dengan keadaan pandemi yang meningkatan resiko mahasiswa tertular penyakit infeksius selama praktik klinik. Berbagai faktor juga berpotensi berhubungan dengan strategi koping mahasiswa keperawatan.Tujuan: Untuk menguji korelasi antara stres dan strategi koping mahasiswa keperawatan di masa pandemi Covid-19, beserta faktor-faktor yang berhubungan dengannya.Metode: Desain deskriptif analitik dengan pendekatan cross-sectional digunakan dalam penelitian ini yang melibatkan 104 mahasiswa keperawatan. Alat ukur yang digunakan yaitu Depression Anxiety Stres Scale-42 (DASS-42) dan Coping Strategies Inventory-Short Form (CSI-SF). Uji statistik menggunakan Independent T-Test, One-way ANOVA, serta Korelasi Pearson.Hasil: Terdapat perbedaan skor rata-rata komponen strategi koping keterlibatan (t=-3.01; p=0.01) dan ketidakterlibatan (t=-0.26; p=0.01) berdasarkan penggunaan alat pelindung diri (APD). Ada perbedaan skor komponen strategi koping keterlibatan berdasarkan pengetahuan dan pencegahan tentang Covid-19 (t=-2.45; p=0.02). Ada korelasi yang signifikan antara umur dengan ketidakterlibatan (r=-0.32; p<0.01) dan ketidakterlibatan berfokus emosi (r=-0.41; p<0.001). Stres berkorelasi signifikan dengan komponen ketidakterlibatan berfokus emosi (r=0.33; p<0.01).Simpulan: Mahasiswa yang berusia lebih tua, pengguna APD memiliki pengetahuan dan pencegahan terkait Covid-19 yang cukup, serta mengalami stres yang lebih parah cenderung menggunakan strategi koping yang lebih baik.Saran: Mahasiswa agar dapat mengelola stres dan menggunakan strategi koping yang positif. Pengkajian terhadap kondisi psikologis mahasiswa dapat dipertimbangkan untuk terus dilakukan selama studi. Penelitian selanjutnya dapat mengembangkan intervensi terhadap penggunaan strategi koping yang tepat pada mahasiswa keperawatan.Kata Kunci: Mahasiswa Keperawatan; Strategi Koping; Stres Subjektif.